2015
DOI: 10.1073/pnas.1506289112
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the in vivo role of trehalose inSaccharomyces cerevisiaeusing theAGT1transporter

Abstract: SignificanceTrehalose is an important molecule for industrial and medical applications. These applications include use as a food additive to increase sweetness and promote freeze-dry preservation. Trehalose is also included in antibody preparations for stabilization during freezing or desiccation. Further, trehalose biosynthesis is required for virulence of fungal pathogens, and, because animal cells do not synthesize trehalose, trehalose biosynthesis is an attractive antifungal target. Despite all of its uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 51 publications
4
75
1
Order By: Relevance
“…A more recent report, however, suggests that trehalose per se has no, or negative, effects on yeast cells and that the effects observed in mutants with defective trehalose synthesis rather are due to a role of trehalose metabolism in central metabolic control 38 . Intracellular trehalose levels have been negatively correlated with specific growth rate of the cells, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…A more recent report, however, suggests that trehalose per se has no, or negative, effects on yeast cells and that the effects observed in mutants with defective trehalose synthesis rather are due to a role of trehalose metabolism in central metabolic control 38 . Intracellular trehalose levels have been negatively correlated with specific growth rate of the cells, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of studies that have previously implicated trehalose as a stress protectant rely on purely correlative data and are based on in vitro studies. Indeed, in a companion paper, Gibney et al demonstrate that introduction of trehalose into naĂŻve yeast cells does not confer tolerance to heat shock, nor does it aid in a variety of other roles to which trehalose has been previously assigned (20).…”
Section: Discussionmentioning
confidence: 99%
“…A third potential indirect mechanism for trehalose-induced desiccation tolerance came from the observation that wild-type cells grown in minimal medium expressing TDH3pr-AGT1 exhibit slower growth rates after addition of trehalose to the media and induced the environmental stress response (ESR) after ∌2 h (20). The ESR induces increased synthesis of additional stress effectors besides trehalose (21).…”
Section: Import Of Extracellular Trehalose Confers Robust Desiccationmentioning
confidence: 99%
“…For example, a recent work with the surface-additive method [33,34] elucidated the unique feature of Tre that underlies its diverse effects on proteins, namely favorable interactions with amide groups and anionic oxygen and unfavorable interactions with aliphatic carbons [35]. The finding stands in marked contrast to a report on the yeast Saccharomyces cerevisiae, in which the authors proved that accumulation of intracellular Tre per se does not improve thermotolerance and proposed that the physiological role of Tre is fundamentally metabolic [36]. Using the mycobacterial Tre-specific transporter, we demonstrated that build-up of intracellular Tre accounts for the OtsA R328H -dependent thermotolerance.…”
Section: Discussionmentioning
confidence: 86%